Methane emissions in growing heifers while eating from a feed bin compared with 24-hour emissions and relationship with feeding behavior - Ashraf Biswas; Ajmal Khan; Dongwen Luo; Arjan Jonker (JDS Communications, 2022)
The objective of the current study was to determine the relationship of daily CH4 emissions estimated during mealtime compared with measured daily CH4 emissions, and determine the relationship with feeding behavior, in growing heifers fed alfalfa silage in respiration chambers. Data from 8 growing cattle (Hereford × Holstein-Friesian) individually housed in 4 respiration chambers and fed ad libitum alfalfa silage delivered in Insentec feed-bins to record feeding behavior and intake were used. The 4 chambers are linked to 1 analyzer, which measures CH4 in each chamber approximately every 3 min. Each 3-min measurement was expressed as grams per day and averaged per 24 h or per time during a meal. A strong correlation (r = 0.88; determined using Deming regression) was observed between CH4 emissions (g/d) during mealtime (276 ± 22.7 g/d) and measured over 24 h (262 ± 24.0 g/d), without apparent systematic bias. Feeding behavior parameters that were correlated with CH4 yield (g/kg dry matter intake) in the current study were a negative correlation with the number of visits to the feed bin (r = −0.45), average meal size (r = −0.57), and average daily eating rate (r = −0.48). In summary, CH4 measured during meals was similar to 24-h measured CH4 output in growing heifers fed ad libitum alfalfa silage in respiration chambers, and some feeding behavior parameters, based on feed bin visits, explained some of the variation in CH4 yield between animals.